1996
DOI: 10.3928/0147-7447-19961001-07
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous vs Modified Phemister Epiphysiodesis of the Lower Extremity

Abstract: Epiphysiodesis of the lower extremity for limb-length discrepancy has been performed on 24 patients by both the modified Phemister and a percutaneous method. The primary complication of epiphysiodesis by both methods was continued growth of the physeal plate (12% and 15%, respectively). Failure of epiphysiodesis was attributed to young skeletal age at surgery in three of five cases. Closer attention to physeal ablation and close follow up should prevent this complication. No angular deformities resulted in any… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…Several surgical procedures have been described for treating mild leg length discrepancy (LLD) [1][2][3][4][5][6][7], all of which have the disadvantage of being more or less irreversible, accomplishing total physeal arrest. The outcome of physiodesis with irreversible methods depends on correctly estimating the age of maturity and the final LLD or leg length.…”
Section: Introductionmentioning
confidence: 99%
“…Several surgical procedures have been described for treating mild leg length discrepancy (LLD) [1][2][3][4][5][6][7], all of which have the disadvantage of being more or less irreversible, accomplishing total physeal arrest. The outcome of physiodesis with irreversible methods depends on correctly estimating the age of maturity and the final LLD or leg length.…”
Section: Introductionmentioning
confidence: 99%
“…Follow-up until skeletal maturity is essential to monitor for recurrence as the failure rate of lateral epiphysiodesis is between 12 and 15%. 32 …”
Section: Discussionmentioning
confidence: 99%
“…However, failure to achieve fusion of the operated physis has been described. Scott et al [17] found three failures of the epiphysiodesis in 20 patients, and Surdam et al [18] reported two failures in 56 patients. Both single-portal and double-portal techniques for percutaneous epiphysiodesis have been described.…”
Section: Discussionmentioning
confidence: 99%